2020
DOI: 10.1109/access.2020.2988915
|View full text |Cite
|
Sign up to set email alerts
|

Antimonotonicity, Chaos and Multidirectional Scroll Attractor in Autonomous ODEs Chaotic System

Abstract: Three-dimensional autonomous ordinary differential equations (ODEs) are the simplest and most important chaotic systems in nonlinear dynamics. In fact, they have been applied in many fields. In this paper, a systematic methodology for analyzing complex behavior of the ODEs chaotic system, as one of the ODEs chaotic systems, the improved TCS which satisfies the condition a 12 a 21 = 0, is proposed. It is dissipative, chaos, symmetric, antimonotonicity and can generate multiple directional (M × N × L) scroll att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 43 publications
(67 reference statements)
0
17
0
Order By: Relevance
“…2); (ii) with the same conditions but the shorter time, multi-scroll attractors can also be obtained, but the number of number is less than the analysis results, which is not a final state and dangerous. Once it is applied to the engineering, it will lead to the wrong effective or immeasurable losses; (iii) the different number scrolls could be presented and identified hysteretic dynamics (imply multiple stability), which have previously observed in some chaotic system [21,26]. When a=1, b=0.5, c=0.85, d=1.5, h=0.1, e=0.6, the coexisting scroll-1 attractors are given in Fig.8.…”
Section: Ivbifurcation and Multiple Scroll Coexisting Attractorsmentioning
confidence: 91%
See 4 more Smart Citations
“…2); (ii) with the same conditions but the shorter time, multi-scroll attractors can also be obtained, but the number of number is less than the analysis results, which is not a final state and dangerous. Once it is applied to the engineering, it will lead to the wrong effective or immeasurable losses; (iii) the different number scrolls could be presented and identified hysteretic dynamics (imply multiple stability), which have previously observed in some chaotic system [21,26]. When a=1, b=0.5, c=0.85, d=1.5, h=0.1, e=0.6, the coexisting scroll-1 attractors are given in Fig.8.…”
Section: Ivbifurcation and Multiple Scroll Coexisting Attractorsmentioning
confidence: 91%
“…Thus, such a novel method for generating M×N×L grid scroll attractors and the existence proof on bounded orbits should be supplied, which are our main objective. Furthermore, the related research on multiple scroll coexisting attractors has been found in no literature before, except [21].…”
Section: A Backgroundmentioning
confidence: 99%
See 3 more Smart Citations